Uncovering CNS Pathways Involved in State Dependent Control of Lower Airway Function - Haxhiu, Musa A.; Balan, Kannan V.; Acquah, Sandra S.; Kc, Prabha (Current Respiratory Medicine Reviews, 2006)
Our understanding of mechanisms involved in worsening of airway function during sleep is incomplete. Therefore, this work is aimed to link central neuronal structures alternating wakefulness and sleep with the neuronal network regulating the activity of airway-related vagal preganglionic neurons (AVPNs). Based on knowledge derived from previous studies, we build a dynamic model in which AVPNs transmit excitatory signals to the intrinsic tracheo-bronchial ganglia controlling airway and lung effector cells. The model indicates that cholinergic outflow to the airways depends on the inhibitory inflow from the monoaminergic and GABAergic cell groups to AVPNs. Inhibitory neurons projecting to the AVPNs are connected to the hypothalamic sleep-promoting region. When activated, this cell group, using GABA and/or galanin as mediators, downregulate activity of inhibitory neurons that project to AVPNs. In airway disorders, diminished inhibitory transmission contributes to impaired withdrawal of cholinergic outflow and long lasting bronchoconstriction. Therefore, changes that occur during sleep result in a shift from inhibitory to excitatory transmission to the AVPNs, leading to increased cholinergic outflow to the airways. This framework can be safely used in explaining sleep-related worsening of bronchial asthma, and might, hopefully, contribute to the further development of research in this field.
Keywords: nocturnal asthma